Prevalence of Syphilis among Pregnant Women Attending Antenatal Care Clinic, Sede Muja District, South Gondar, Northwest Ethiopia - Getachew Yideg Yitbarek; Belete Achamyelew Ayele (Hindawi Limited, 2019)
Background. Syphilis is a disease caused by bacteria called Treponema pallidum. Major rout of transmission of this bacterium was through sexual and contact with mucocutaneous lesion. Untreated syphilis during pregnancy can greatly affect pregnancy outcome, resulting in spontaneous abortion and stillbirth. Objective. The objective of the study was to determine the seroprevalence of syphilis and associated factors among pregnant women attending antenatal care unit at Sede Muja district, Northern Ethiopia. Methods and Materials. Facility based cross-sectional study was conducted from November 2018 to January 2019 in two health centers from Sede Muja district, Northwest Ethiopia. The study included a total of 210 participants. The entire participants were recruited by systematic random sampling method after proportional allocation of the sample size in the two health centers. Sociodemographic and clinical data were collected by semistructured questioner. Two milliliter of blood was collected to determine seroprevalence of syphilis using VDRL test method. The data was analyzed by using SPSS version 21. The association between independent and dependent variables was determined using chi-square. P-value less than 0.05 was considered as statistically significant. Result. Seroprevalence of syphilis was found to be 1.9% (95 CI, 0.5-3.5%). Women with multiple sexual partners and late trimester of pregnancy during first ANC visit were found to be significantly associated with seropositive syphilis. Conclusion. Syphilis remains a major problem in the study area. Seroprevalence of syphilis was significantly associated with women who have multiple sexual partners and late first ANC visit attendees in the study area. Therefore it is recommended to give health education about syphilis etiology and transmission as well as creating awareness about the importance of early ANC visit and follow-up regarding syphilis prevention.